Russian Pitch-Class Set Analysis and the Music of Webern - Philip A. Ewell (Gamut: Online Journal of the Music Theory Society of the Mid-Atlantic, 2013)
Prompted by a live performance of Webern’s Op. 6 in Moscow, in 1965, brother and sister Yuri Kholopov and Valentina Kholopova began to analyze the music of Webern; from 1965 to 1970 they wrote two books thereon. Working from scores and a few writings by Europeans (i.e., Stockhausen, Pousseur, Metzger, Kolneder, and Karkoschka), Valentina Kholopova devised a system of pc set analysis, which Yuri later named “hemitonicism.” She first presented her findings to the Soviet “Union of Composers” in the early 1970s, and then published a follow-up article in 1973. In the present essay, the author explicates this important development in Russian music theory. In hemitonicism, octave, enharmonic, transpositional, and inversional equivalence are all operative. There are two types of hemitonicism: fields (the continuous filling in, by semitone, of some portion of the chromatic scale), and groups (five three-note and five four-note archetypal pc sets that feature at least one semitone—thus, there are ten total archetypal sets in the hemitonic system). By looking at some of the Kholopovs’ analyses, and providing some new analyses, the author shows that their system bears many resemblances to American pc set analysis, while also having many interesting and significant differences. In an appendix, the author provides a complete translation into English of the chapter on “hemitonicism,” from Valentina Kholopova’s and Yuri Kholopov’s Russian-language book, The Music of Webern (1999). This article is part of a special, serialized feature: A Music-Theoretical Matrix: Essays in Honor of Allen Forte (Part IV).